Hepatoprotectivity and an Antioxidant Study of Ipomoea hederacea on Experimentally Induced Hepatotoxic Rats - mathi1*, Ruckmani Devi S1, M. Chitra2; P. Jaya (Recent Research in Science and Technology, 2010)
Ipomoea hederacea extract, a novel hepatoprotective drug has been shown to provide an antioxidant potential against carbon tetra chloride treated experimentally induced hepatotoxitic rats in comparison with standard hepatoprotective drug silymarin. Significantly raised levels of serum bilirubin, lipid peroxides and decreased activities of antioxidant enzymes such as superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase andÂ decreased activities of gamma glutamyl transpeptidase were observed and it was nearer toÂ normal in Ipomoea hederacea administrated experimentally induced hepatotoxic rats. These observations clearly suggested the hepatoprotectivity and antioxidant property of Ipomoea hederacea.